The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/biot.201200076
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐function studies with G protein‐coupled receptors as a paradigm for improving drug discovery and development of therapeutics

Abstract: There are a great variety of human membrane proteins, which currently form the largest group of marketed drug targets. However, despite the advances in drug design, promiscuity between drug molecules and targets often leads to undesired signaling effects, which result in side effects from treatment. In this review, one family of membrane proteins – G protein-coupled receptors (GPCRs) – is used as a model to review experimental techniques that may be used to examine the activity of membrane proteins. As these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 114 publications
0
15
0
1
Order By: Relevance
“…As a consequence, the largest group of therapeutic agents today target GPCRs (McNeely et al 2012). In addition, some of the landmark discoveries in cell biology and receptor signal transduction were derived from studies of GPCR signalling.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the largest group of therapeutic agents today target GPCRs (McNeely et al 2012). In addition, some of the landmark discoveries in cell biology and receptor signal transduction were derived from studies of GPCR signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low expression in native systems, the poor quality of heterologous expression, difficult purification, and instability, studying these receptors in vitro is challenging (Allen, Ribeiro, Horuk, & Handel, 2009;Doré et al, 2011;Jones, Greene, Grygon, Doranz, & Brown, 2008;Langelaan, Ngweniform, & Rainey, 2011;McNeely, Naranjo, & Robinson, 2012;Wisedchaisri, Reichow, & Gonen, 2011). The previous purification of functional A 2 aR has shown that in order to retain its α-helical content and ligand-binding activity, the presence of cholesteryl hemisuccinate (CHS) is required when purified in dodecylmaltoside (DDM) (O'Malley et al, 2007).…”
Section: Membrane Mimetic Environmentsmentioning
confidence: 99%
“…Zudem unterliegen Thyronamine selbst einer schnellen Veränderung durch Metabolisierung [28]. Aufgrund ihrer zentralen Rolle für die Signaltransduktion sind die möglichen Thyronamin-Rezeptoren, GPCRs, äußerst interessante Zielmoleküle für eine pharmakologische Intervention [21]. Im Zusammenhang mit Thyronaminen lässt sich die Entwicklung neuer Therapeutika zur Regulation z.B.…”
Section: Beurteilung Des Schilddrüsenhormonlabors ▼unclassified